METHODOLOGICAL BASIS OF IMPLEMENTATION OF INNOVATIVE METHODS IN CORPORATE MANAGEMENT (Marketing Journal, 2025)
This article analyzes the strategic importance of implementing innovative management methods in joint -stock companies. The study highlights issues related to process reorganization, the formation of responsibility centers, the improvement of the value chai n, and the introduction of open communication mechanisms with stakeholders. Based on the analysis, tables and diagrams were developed to illustrate the main directions of innovative approaches and their practical value in enhancing corporate efficiency.
Keywords: corporate governance; innovative methods; methodology; digital transformation; innovation strategy; joint -stock companies; financial efficiency; corporate strategy; competitiveness. 171